IMPLEMENTATION OF COMPETENCY-BASED LEARNING PROGRAMS IN PREPARING GRADUATES FOR EMPLOYMENT AT STATE VOCATIONAL HIGH SCHOOL 4 TEBING TINGGI - Rahayu, Suri; Ritonga, Syahfruddin; Masitho Batubara, Beby (Pena Cendekia Insani, 2026)
This study aims to analyze the implementation of competency-based learning programs in preparing graduates for employment at State Vocational High School 4 Tebing Tinggi. Competency-based learning is an educational approach that emphasizes the mastery of knowledge, skills, and work attitudes in accordance with the needs of the business and industrial sectors. This study employs a qualitative approach with a descriptive method. Data collection techniques include observation, in-depth interviews, and documentation. The research informants consist of the principal, teachers, and students of State Vocational High School 4 Tebing Tinggi. The results indicate that the implementation of competency-based learning programs at State Vocational High School 4 Tebing Tinggi has generally been carried out in accordance with established standards, as reflected in the application of a competency-based curriculum, the integration of theoretical and practical learning, and the implementation of industrial work practice. However, the implementation has not yet been fully optimal due to several inhibiting factors, including limited practical facilities and infrastructure, a lack of continuous teacher training, minimal involvement of the business and industrial sectors, and differences in competency levels among students.